Mapping World Language: is Proto-Indo-European the First one? - Elim, Hendry Izaac (Pattimura University, 2021)
The origin of language was very complicated in terms of its sources from human being characters and its evolution carried out by over millions of human being generations from ancient creatures to current modern humankind. In this simple work, a language mapping was extracted from many different scientific heritages and references study so that the obvious understanding of it can be easily viewed even by an ordinary people. Furthermore, the relationship among many diversities of language is identified conveniently. This piece of research suggests that language was started from the very first beginning of human being creature on earth. In addition, it is eventually assumed that such “first language” is well-known as Proto-Indo-European (PIE) with the limitations of Asian and Africa language historical evidences. The reason might be associated with the educational and cultural system of life in both continents.